Enhanced fluorescence detection of miRNA-16 on a photonic crystal. Issue 16 (21st August 2015) - Frascella, F.; Ricciardi, S.; Pasquardini, L.; Potrich, C.; Angelini, A.; Chiadò, A.; Pederzolli, C.; De Leo, N.; Rivolo, P.; Pirri, C. F.; Descrovi, E.
<x xml:space="preserve">Abstract</x> We report a novel sensing method for fluorescence-labelled microRNAs (miRNAs) spotted on an all-dielectric photonic structure.